2017
DOI: 10.1111/ele.12826
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial communities drive the resistance of ecosystem multifunctionality to global change in drylands across the globe

Abstract: The relationship between soil microbial communities and the resistance of multiple ecosystem functions linked to C, N and P cycling (multifunctionality resistance) to global change has never been assessed globally in natural ecosystems. We collected soils from 59 dryland ecosystems worldwide to investigate the importance of microbial communities as predictor of multifunctionality resistance to climate change and nitrogen fertilisation. Multifunctionality had a lower resistance to wetting-drying cycles than to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
197
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(213 citation statements)
references
References 49 publications
11
197
3
2
Order By: Relevance
“…Land degradation is a global problem that is leads to substantial changes in soil biodiversity and ecosystem functions and services (Caravaca, Lozano, Rodriguez‐Caballero, & Roldan, ; Delgado‐Baquerizo et al, ). Revealing the temporal responses of particular bacterial groups to soil perturbations and their contributions to ecosystem multifunctionality is pivotal to understand the maintenance of microbial diversity and microbe‐driven ecosystem processes (Delgado‐Baquerizo et al, ). In this study, we found that native bacterial communities exhibited stronger resilience to the introduced microbial consortium than to the legume plants growing in a multicontaminated agricultural soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Land degradation is a global problem that is leads to substantial changes in soil biodiversity and ecosystem functions and services (Caravaca, Lozano, Rodriguez‐Caballero, & Roldan, ; Delgado‐Baquerizo et al, ). Revealing the temporal responses of particular bacterial groups to soil perturbations and their contributions to ecosystem multifunctionality is pivotal to understand the maintenance of microbial diversity and microbe‐driven ecosystem processes (Delgado‐Baquerizo et al, ). In this study, we found that native bacterial communities exhibited stronger resilience to the introduced microbial consortium than to the legume plants growing in a multicontaminated agricultural soil.…”
Section: Discussionmentioning
confidence: 99%
“…Aboveground–belowground linkages have important implications for restoration ecology in that they play vital roles in driving ecosystem structure and functioning, including the cycling of carbon and nutrients (Kardol & Wardle, ). Microbial ecosystems can exhibit remarkable resistance and resilience in response to various environmental alterations, such as global climate change (Delgado‐Baquerizo et al, ; Szekely & Langenheder, ), soil contamination (Jiao, Chen, et al, ; Jiao, Liu, et al, ), and pH fluctuation (Feng et al, ). In our experiment, we found that soil microcosms were influenced by introducing the contaminant‐degrading microbial consortium in the early phase, but they quickly recovered their compositional β ‐diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, soil pH values from our soils were also negatively correlated with the relative abundance of Basidiomycota (Supporting Information Table S4), a group of fungi found typically in acidic forested soils, but positively correlated with Actibobacteria and Gemmatimonadetes, and the fungal phyla Glomeromycota and Chytridiomycota (Supporting Information Table S4). Proteobacteria, particularly γ-Proteobacteria, have been shown to be important drivers of soil functioning in both field and microcosm studies from Australian soils (Delgado-Baquerizo et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Data availability and references to the original protocols for each dataset are available in Supporting Information Table S2. For example, in the particular case of soil microbial communities, we gathered information for 101 plots including the 79 sites in Maestre et al (2015) and the 22 sites in Delgado-Baquerizo et al (2017).…”
Section: Methodsmentioning
confidence: 99%